HNRNPA2B1 regulates the epithelial–mesenchymal transition in pancreatic cancer cells through the ERK/snail signalling pathway - Dai, Shengjie (Cancer Cell Int, 2017)
BACKGROUND: Heterogeneous nuclear ribonucleoprotein A2B1 (HNRNPA2B1) is closely related to tumour occurrence and development, oncogene expression, apoptosis inhibition and invasion and metastasis capacities. However, its function in the epithelial–mesenchymal transition (EMT) of pancreatic cancer is not fully understood. METHODS: By comparing various wild-type pancreatic cancer cell lines, we determined which have a higher expression level of HNRNPA2B1 accompanied by the higher expression of N-cadherin and vimentin and lower expression of E-cadherin. Therefore, to elucidate the role of HNRNPA2B1 in EMT, we generated models of HNRNPA2B1 knockdown and overexpression in different types of pancreatic cancer cell lines (MIA Paca-2, PANC-1 and Patu-8988) and examined changes in expression of EMT-related factors, including CDH1, CDH2, vimentin and snail. RESULTS: The results show that HNRNPA2B1 promotes EMT development by down-regulating E-cadherin and up-regulating N-cadherin and vimentin, and also stimulates the invasion capacity and inhibits viability in human pancreatic cancer cell lines, the similar results in vivo experiments. Moreover, we found that HNRNPA2B1 likely regulates EMT progression in pancreatic carcinoma via the ERK/snail signalling pathway. CONCLUSIONS: The results of this work suggest that HNRNPA2B1 inhibition has potential antitumour effects, which warrants in-depth investigation.